2021
DOI: 10.1002/cb.1931
|View full text |Cite
|
Sign up to set email alerts
|

A superiority–inferiority hypothesis on disparagement humor: The role of disposition toward ridicule

Abstract: The present paper adopts and substantiates a superiority-inferiority hypothesis on disparagement humor generation and appreciation. Two between-subjects (identification with a character acting as victimizer or victim) experiments address disparaging humorous advertising effectiveness, providing a novel perspective on very old questions. Perceived superiority and inferiority autonomously mediate the relationship between a disparaging advertisement and perceived humorousness. Individuals with high superiority mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…To our knowledge, no study has examined the moderating effects of superiority as an individual characteristic on humor effects. Hatzithomas et al (2021) found that superiority mediated the relationship between exposure to a disparaging but funny advertisement and subsequent attitudes toward the brand (Hatzithomas et al, 2021). However, superiority was conceptualized as identification with the victimizer in the advertisement rather than as a characteristic of the recipient themselves.…”
Section: Superiority As a Moderatormentioning
confidence: 99%
“…To our knowledge, no study has examined the moderating effects of superiority as an individual characteristic on humor effects. Hatzithomas et al (2021) found that superiority mediated the relationship between exposure to a disparaging but funny advertisement and subsequent attitudes toward the brand (Hatzithomas et al, 2021). However, superiority was conceptualized as identification with the victimizer in the advertisement rather than as a characteristic of the recipient themselves.…”
Section: Superiority As a Moderatormentioning
confidence: 99%
“…Entertaining consumers is a consistently important objective for branded content on social media (Gavilanes et al, 2018) Prior research also indicates that about half of all branded videos contain humor (Karpinska-Krakowiak, 2020). Prior branded video research has not delved into distinct types of humor, but advertising research suggests that humor in advertising takes a wide variety of forms, including disparagement (Hatzithomas et al, 2021) and aggression (Swani et al, 2013) that evoke humor by allowing consumers to perceive a sense of their own superiority, as well as surprise and incongruity (Alden et al, 2000), which result in humor perceptions once the arousal sparked by these elements gets successfully resolved. However, the funny branded videos and humorous ads addressed in prior research are not necessarily narratives, like short film ads are.…”
Section: Funny Plotsmentioning
confidence: 99%